Application of the AHP Matrix to correlate Lean Safety tools with ISO 45001:2018 requirements - de Oliveira Menezes, Michelle; Agra Pimentel, Cristiane (Brazilian Journal of Production Engineering, 2026)
The implemented Occupational Health and Safety Management System provide benefits to business performance by establishing requirements that ensure safety is integrated into production processes. Lean tools serve as allies in implementation, sharing a common focus on performance and safety. The objective of this study is to apply the multicriteria decision-making method Analytic Hierarchy Process (AHP) to correlate lean safety tools with the requirements of ISO 45001:2018. The applied method consisted of the AHP stages: problem definition, hierarchy structuring, matrix construction, pairwise comparisons, and obtaining final weights and priorities. The most relevant requirements identified were Operation, Improvement, and Planning. The tools most relevant to these requirements were 5S, VSM, SMED, and Poka Yoke. The correlation demonstrated the applicability of lean safety tools in the certification process for ISO 45001.
Keywords: lean tools; ISO 45001:2018; AHP